Menilik Ulang Resiliensi: Covid-19 dan Pariwisata di Kaliurang Yogyakarta - Mulyasari, Runavia (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The process of recovering when experiencing disasters and crises is often considered an individualised process. The Covid-19 pandemic in the past two years has had a major impact on various sectors of the world, and the most affected is tourism. Many studies on pandemic conditions and tourism have been conducted with a focus on the impact of the pandemic. For this reason, it is necessary to look back at the resilience process carried out by tourism actors and the tourism community in dealing with the pandemic. Yogyakarta, especially Kaliurang, is the most affected area due to the pandemic. This study attempts to invite a revisit of tourism resilience in Kaliurang. Ethnography is used to capture the resilience efforts made by the community and tourism actors in Kaliurang. The research shows a change in community structure and agency development at the individual and group levels. Both structure and agency simultaneously help the process of community resilience, which is then developed into resilience in the tourism sector.